2020
DOI: 10.1101/2020.01.11.20017186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potential cost-effectiveness of controlling dengue in Indonesia using wMel Wolbachia released at scale: a modelling study

Abstract: Background Release of virus-blocking Wolbachia infected mosquitoes is an emerging disease control strategy that aims to control dengue and other arboviral infections. Early entomological data and modelling analyses have suggested promising outcomes and wMel Wolbachia releases are now ongoing or planned in 12 countries. To help inform potential scale-up beyond single city releases, we assessed this technologys cost-effectiveness under different programmatic options. Methods Using costing data from existing Wol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Comparing all scenarios, the result confirmed that combining vaccination with a Wolbachia program within an integrated approach was considered to be the most cost-effective intervention. A previous study investigated the potential cost-effectiveness of a Wolbachia program in Indonesia, which confirmed that Wolbachia released in high density urban areas is expected to be highly cost-effective and could potentially be a cost-saving intervention to prevent dengue infections [47]. In particular, regions with a strong public health infrastructure, fiscal capacity, and community support should be prioritized.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Comparing all scenarios, the result confirmed that combining vaccination with a Wolbachia program within an integrated approach was considered to be the most cost-effective intervention. A previous study investigated the potential cost-effectiveness of a Wolbachia program in Indonesia, which confirmed that Wolbachia released in high density urban areas is expected to be highly cost-effective and could potentially be a cost-saving intervention to prevent dengue infections [47]. In particular, regions with a strong public health infrastructure, fiscal capacity, and community support should be prioritized.…”
Section: Discussionmentioning
confidence: 84%
“…The results of sensitivity analysis in our study shows that dengue infection rates, underreporting factors for hospitalization, cost of the Wolbachia program, vaccine price, vaccine efficacy, and case fatality rates were considered to be the most influential parameters affecting the cost-effectiveness of integrated dengue vaccination programs. Previous model analyses found the same parameters being most influential in sensitivity analyses [8,30,[47][48][49][50].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation